PERAN GURU PAI DALAM MENCEGAH PAHAM RADIKALISME BAGI SISWA DI MTS IRSYADUL ANAM KIYUDAN SELOMARTANI KALASAN SLEMAN YOGYAKARTA - Saprialman Saprialman; Ferianto Ferianto; Yuli Salis Hijriyani; Khairil Aswan (Universitas Islam Negeri Sumatera Utara Medan, 2022)
This research departs from the phenomenon of radicalism that occurs in society, especially in the world of education. The understanding of radicalism is an understanding that must be immediately overcome and avoided from students because it is contrary to the Islamic religion which is rahmatan lil 'alamin and not in accordance with the purpose of organizing Islamic education itself. The focus of the problem in this study is